Exploring Sensory Marketing in E-Commerce: The Role of Visual and Auditory Cues on Customer Engagement and Purchase Intention - Ika Susilawati; Ika Susilawati; Sri Murni Setyawati; Nur Choirul Afif (Universitas Mercu Buana, 2026)
Objective: This study aims to examine the role of visual cues and auditory cues as part of sensory marketing strategies in influencing customer engagement and purchase intention among Indonesian e-commerce consumers.Methodology: A quantitative explanatory research design was employed. Data were collected through an online survey of 310 active e-commerce users in East Java. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) via SmartPLS.Finding: The results indicate that visual cues significantly affect purchase intention both directly and indirectly through customer engagement. In contrast, auditory cues do not have a significant direct effect but demonstrate a significant indirect influence through engagement. This highlights engagement as a key psychological mechanism linking sensory marketing to purchase intention.Conclusion: The study extends the application of the Stimulus–Organism–Response (SOR) framework and sensory marketing literature in the digital context of emerging markets. Practically, it provides strategic implications for e-commerce platforms to prioritize visual quality while leveraging auditory elements as emotional enhancers, thereby strengthening consumer engagement and fostering purchase intentions through enhanced customer engagement.